Study on the bearing characteristics of overrun hydraulic support under impact loading - Cao, Lianmin; Yan, Ping; Xi, Wenxian; Zhang, Xiaowei; Jin, Xin; Yang, Hongjuan (Frontiers in Earth Science, 2023)
In order to study the effects of stress change and adaptability of the overrun hydraulic stent under impact load, the rigid–flexible coupling numerical model of the stent is established using multi-body dynamics simulation software ADAMS. In the model, the stent is flexibilized using the HyperMesh module, and the column and jack are equivalently replaced with a spring damping system. By applying impact loads to different positions above the front roof beam of the stent, the dynamic response characteristics of the column and the articulation point are obtained at different positions with different strengths. The results show that when the impact load is applied to different positions of the front roof beam, the steady-state response force of the column shows an overall “M" distribution, and along the length direction of the roof beam, the steady-state response force of the column shows an upward trend, and the maximum steady-state response force of the column is 547 kN at point (1, 6); when the impact load is applied to both sides of the front roof beam, the response at the articulation point is greater, resulting in a higher maximum simple harmonic response at that articulation point. When the impact load acts on both sides of the front roof beam, the response of the articulation point is greater, with a maximum simple harmonic response coefficient of 0.75 and a maximum excitation response coefficient of 0.28; when the impact loads of different strengths act on the whole front roof beam, the force acting on the column and pin shaft at the articulation point will produce a large impact, reducing its adaptability. To address this, we can consider changing the top plate stress conditions using methods like high-pressure injection of water and control the gradual and slow release of the top plate stresses. The results of the study provide a reference for the structural strength design and reliability analysis of the hydraulic support, which is of practical significance and value for improving the safe mining of the coal mining face.